Survey on efficacy of chloroformic extract of Artemisia annua against Giardia lamblia trophozoite and cyst in vitro - Golami, Shirzad (J Parasit Dis, 2014)
Giardiasis is a parasitic cosmopolitan disease that the rate of infection in developing countries is considerable. This infection directly is associated with poor hygienic conditions, poor water quality control, and overcrowding. Reinfection and drug resistance are two major problems in endemic areas. Recently, researchers are concentrating on herbal drugs as a proper solution. Therefore, the objective of the present study was to survey on efficacy of chloroformic extract of Artemisia annua against Giardia lamblia trophozoite and cyst in vitro. G. lamblia cysts were prepared from faces of giardiasis patients from different hospitals of Mazandaran Medical University. Four concentrations (1, 10, 50 and 100 mg/ml) of chloroformic extract of A. annua were utilized for 1, 5, 30, 60 and 180 min. Viability of G. lamblia cysts was confirmed by 0.1 % Eosin staining. Cyst and trophozoite contact (intermix) of G. lamblia with extract of A. annua with variant concentrations (1, 10, 50 and 100 mg/ml) after 1 and 180 min caused following cyst and trophozoite elimination rates: (67, 69, 71 and 73 %), (65, 67, 67 and 72 %), (94, 96, 97 and 99 %) and (100, 100, 100 and 100 %), respectively. Authors from the current investigation draw a conclusion that chloroformic extract of A. annua has the ability to eliminate G. lamblia cysts and trophozoites in vitro.